Multimedia-based tactical learning in soccer - Leser, R.; Uhlig, J.; Uhlig, M. (International Journal of Computer Science in Sport, 2009)
Among other things, the modern game of football is characterised by pronounced group and team-oriented tactical abilities. Of particular importance is thereby zone defence or zone coverage, which is used by almost all teams playing at an elevated level of performance. In contrast to man-marking, this more efficient form of organisation is very difficult to convey, as attention must at any given time be directed toward several different aspects (ball, opponent, team-mates) and must dynamically adapt to every game situation. The authors describe a project that focussed on that thematic and which resulted in an application for practical use.